Topic-Level Effectiveness of the Entrepreneur Development Class in Indonesia's Wirausaha Merdeka Program - Dhanang Eka Putra; Hariyono Rakhmad; Dessy Putri Andini; Refa Firgiyanto; Huda Ahmad Hudori; Elly Antika; Mochamad Rizal Umami; Nanik Anita Mukhlisoh; Dwi Putro Sarwo Setyohadi; Risse Entikaria Rachmanita (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study evaluates the effectiveness of the Entrepreneur Development Class (EDC), the foundational learning phase of Indonesia’s Wirausaha Merdeka program, by examining topic-level learning gains across ten instructional modules. The study responds to persistent limitations in entrepreneurship education evaluation, including the dominance of perception-based measures, the reliance on aggregate outcomes, the limited empirical evidence on Wirausaha Merdeka, and the limited use of normalized gain analysis in assessing instructional effectiveness. Design/methodology/approach – A quantitative one-group pre-test–post-test design was employed using a complete cohort of 550 students from twelve vocational higher education institutions participating in the 2024 Wirausaha Merdeka program coordinated by Politeknik Negeri Jember. Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov test, paired-samples t-tests, Hake’s normalized gain (g), and Cohen’s d effect size. Findings/Results – The overall mean score increased from 70.40 to 95.25, yielding a high normalized gain (g = 0.84) and a very large effect size (d = 1.70). Business Idea Development emerged as the most effective module (g = 0.90), whereas Pondasi Bisnis Berkah produced the lowest gain (g = 0.68). The findings suggest that instructional effectiveness varies across competency domains and is influenced by both baseline knowledge and the characteristics of the learning outcomes targeted. Originality/Value – This study contributes to entrepreneurship education research by introducing a topic-level evaluation framework that combines objective knowledge assessment, normalized gain analysis, effect-size estimation, and significance testing. The approach provides a more diagnostic understanding of instructional effectiveness than aggregate program-level measures and offers practical guidance for curriculum improvement, quality assurance, and policy evaluation in large-scale vocational entrepreneurship programs.